Particle size affects pharmacokinetics of milled oxycodone hydrochloride tablet products following nasal insufflation in nondependent, recreational opioid users - Saeid Raofi; Minori Kinjo; Dajun Sun; Zhichuan Li; Heather Boyce; Karthika Natarajan; Mitchell Frost; Liang Zhao; Markham Luke; Robert Lionberger; Debra Kelsh; Myong‐Jin Kim (Wiley, 2021)
Abstract This study assessed the impact of product particle sizes (fine: 106-500 µm; coarse: 500-1000 µm) on oxycodone pharmacokinetics (PK) following nasal insufflation of milled oxycodone extended‐release (ER) abuse‐deterrent (AD) tablets using immediate‐release (IR) non‐AD product as reference. Additionally, this study assessed the effects of different excipient to drug ratio (EDR) by comparing two products with fine particle size but different EDRs, again using IR non‐AD as the control. Thirty milligrams of oxycodone were administered in each treatment. Coarsely milled 30 mg ER tablets demonstrated significantly lower maximum plasma concentration (Cmax) and partial areas under the concentration‐time curve (AUCs) than those of the finely milled IR tablets. Finely milled ER tablets demonstrated similar Cmax and partial AUCs but higher total systemic exposures than those of finely milled IR tablets. Finely milled 80 mg ER tablets were bioequivalent to IR tablet on all parameters. The finely milled 30 mg ER tablet was not bioequivalent to the coarsely milled 30 mg ER tablet and had higher values for all parameters. The finely milled 30 mg ER tablets (EDR 6.9) showed no PK differences with finely milled 80 mg ER tablets (EDR 4.9). No serious adverse events were reported. The study demonstrated a significant effect of particle sizes (106-1000 µm) on PK of milled and insufflated oxycodone ER AD tablets. EDR difference did not have any significant effects on the PK of finely milled oxycodone ER AD tablets. Particle size distribution should be considered when nasal AD properties of opioid drug products are investigated during drug development.